A integração das tecnologias de informação e comunicação na escola: o projto político pedagógico nesse contexto - Castro, Marcia Ferreira de [UNESP]; Lemes, Sebastiao de Souza [UNESP] (My University, 2014)
This study aims to analyze the possibilities of integration of new information and communication technologies (ICT) in teaching and learning in a school of public elementary school Municipal Araraquara. This is a survey based on a qualitative approach, which has a strategy Case Study. Made an analysis of the Curriculum Guidelines and Policy Project (PPP) school selected, in order to check how the school addresses the issue of the use of new technologies in the educational process. For the analysis of the Curriculum Guidelines and Educational Policy Project found that the school has studied a concern to make use of ICT in teaching and learning, featuring an awareness of the importance of technology in education, but does not describe ways to integrate curricularmente them. The integration of new technologies into the curriculum requires a systematic reflection about their goals, their technical and content chosen. Not only is working with new technologies aimed at digital inclusion of students, but we need to integrate the school into their curricular, integrate them into the process of teaching and learning. Today ICT configure themselves into a new form of language, essential for knowledge representation and, if so, their presence in the school curriculum is crucial.

O presente trabalho tem como objetivo analisar as possibilidades de integração das novas tecnologias de informação e comunicação (TIC) no processo de ensino-aprendizagem em uma escola de Ensino Fundamental da Rede Municipal de Araraquara. Trata-se de uma pesquisa fundamentada numa abordagem qualitativa, que tem como estratégia o Estudo de Caso. Fez-se uma análise das Diretrizes Curriculares e do Projeto Político Pedagógico (PPP) da escola selecionada, com o intuito de verificar como a escola aborda o tema do uso das novas tecnologias no processo educativo. Pela análise feita das Diretrizes Curriculares e do Projeto Político Pedagógico constatamos que a escola estudada tem uma preocupação em fazer uso das TIC no processo de ensino e aprendizagem, o que caracteriza uma conscientização da importância das tecnologias na educação, porém não descreve formas de integrá-las curricularmente. A integração das novas tecnologias no currículo exige uma reflexão sistemática acerca de seus objetivos, de suas técnicas e dos conteúdos escolhidos. Não é somente trabalhar com as novas tecnologias visando à inclusão digital dos alunos, mas é preciso que a escola as integre nas atividades curriculares, ou seja, integrá-las ao processo de ensino e aprendizagem. Hoje as TIC se configuram em uma nova forma de linguagem, essencial para a representação do conhecimento e, nesse caso, sua presença no currículo escolar é fundamental.
The integration of information and communication technologies in schools: the political pedagogical project in this context
Keywords: Information and Communication Technologies; Education; Learning; Political Pedagogical Project; Tecnologias de Informação e Comunicação; Ensino; Aprendizagem; Currículo